A Long Journey Ahead: Long Non-coding RNAs in Bacterial Infections - zur Bruegge, Jennifer; Einspanier, Ralf; Sharbati, Soroush (Frontiers in Cellular and Infection Microbiology, 2017)
Bacterial pathogens have coevolved with their hosts and acquired mechanisms to circumvent defense mechanisms of host cells. It was shown that bacteria interfere with the expression of mammalian microRNAs to modify immune signaling, autophagy or the apoptotic machinery. Recently, a new class of regulatory RNAs, long non-coding RNAs (lncRNAs), was reported to have a pivotal role in the regulation of eukaryotic gene expression. A growing body of literature reports on specific involvement of lncRNAs in the host cell response towards bacterial infections. This mini review summarizes recent data that focuses on lncRNA function in host cells during bacterial infection and provides a perspective where future research in this regard may be going.